Treatment of Agitation With Lorazepam in Clinical Practice: A Systematic Review - Amore, Mario; D'Andrea, Mariella; Fagiolini, Andrea (Frontiers in Psychiatry, 2021)
Acute agitation is a frequent occurrence in both inpatient and outpatient psychiatric settings, and the use of medication to calm a patient may be warranted to mitigate the situation. Lorazepam is a benzodiazepine that is widely used for management of acute agitation. Despite its widespread use, there is remarkably little clinical evidence for the benefits of lorazepam in acute agitation. We performed a systematic review with focus on lorazepam, including all randomized clinical trials on lorazepam in mental and behavioral disorders, excluding studies on dementia and pediatric patients and in mixed conditions. A total of 14 studies met inclusion criteria. Eleven of the trials were in patients with mental and behavioral disorders, and the remaining 3 trials in an emergency department specific setting. Most trials generally found improvements across a variety of outcomes related to agitation, although there was some disparity if specific outcomes were considered. In the five studies with haloperidol, the combination of lorazepam and haloperidol was superior to either agent alone, but with no differences between monotherapy with the individual agents. In the two studies comparing lorazepam to olanzapine, olanzapine was superior to lorazepam, and both were superior to placebo. In the studies in emergency settings, droperidol was superior to lorazepam, and midazolam was superior over lorazepam. As expected, the safety of lorazepam among the different studies was consistent with its well characterized profile with dizziness, sedation and somnolence being the most common adverse events. Based on this structured review, lorazepam can be considered to be a clinically effective means of treating the acutely agitated patient.